The Role of the Lysophosphatide Acid in the Pathogenesis of Bronchial Asthma (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Lysophospholipids are bioactive lipid mediators localized in cell membranes. They influence cell proliferation, differentiation, survival, migration, adhesion, invasion and morphogenesis, and are also associated with neurogenesis, angiogenesis, fibrogenesis and tumorigenesis.